A multi-case study of secondary principal practices supporting co-teaching in the context of the least restrictive environment - Howser, Debora L. (Kansas State University, 2015)
Educational leadership is challenged with meeting the requirements of No Child Left Behind (NCLB) of 2001 and Individuals with Disabilities Education Improvement Act (IDEIA) of 2004. The focus on accessibility and accountability is resulting in an increase in the number of students with disabilities receiving specialized instruction within the least restrictive environment (LRE) of the general education classroom. To support students in the LRE, many schools are implementing the service delivery model of co-teaching, or pairing a special educator with a general educator, to provide core instruction with appropriate special education services to students with special needs. The purpose of this case study was to investigate what practices of principals are deemed most supportive to teachers engaged in a co-teaching service delivery model. The qualitative, multi-case study was designed to analyze perceptions of district level general education administrators, district level special education administrators, building principals, co-teaching coaches, and co-teaching partners who participated in the Kansas Co-Teaching Initiative. Data were obtained primarily through interviews of the participants. Demographic surveys, building schedules and field notes served as additional information for analysis and the interpretation of the data. The over-arching research question for this study was: “What practices of principals provide the most meaningful support to collaborative co-teaching in the context of the least restrictive environment?” Sheard and Kakabadse’s nine Key Elements of Effective Teams (2002, 2004) formed the framework for the study. These key elements also guided the research sub-questions. Data collected through the study revealed sixty patterns across the key elements of effective teams. When analyzed, the patterns yielded three themes: 1) principals arranged and protected time during the daily schedule for collaboration between co-teaching partners, 2) principals paired co-teachers together with careful consideration for compatibility, and 3) principals established and maintained a culture of professional growth.
Keywords: Co-Teaching; Least restrictive environment; Secondary principal practices; Educational leadership; Kansas Co-Teaching Initiative; Collaborative teams; Educational leadership (0449); Secondary Education (0533); Special Education (0529)